Co-occurrence of PTSD and affective symptoms in a large sample with childhood trauma subtypes: A network analysis - Jin, Yu; Xu, Shicun; Hu, Zhishan; Li, Jiaqi; Li, Hui; Wang, Xiaofeng; Sun, Xi; Wang, Yuanyuan (Frontiers in Public Health, 2023)
Background: Exposure to childhood trauma (CT) is associated with various deleterious mental health outcomes, even increasing the risk of suicidal behaviors. This is the first study to investigate the different effects of three types of CT, including sexual abuse (SA), physical abuse (PA), and emotional abuse (EA), on potential psychopathological symptoms among college students. Methods: A total of 117,248 students from 63 Chinese colleges participated in this study. There were 1.24% EA (N=1,191), 1.32% PA (N=1,272), and 3.62% SA (N=3,479). CT, depressive symptoms, anxiety symptoms, and post-traumatic stress disorder (PTSD) symptoms were measured by the Childhood Trauma Questionnaire-Short Form, Patient Health Questionnaire-9, Generalized Anxiety Disorder Scale-7, and Trauma Screening Questionnaire, respectively. Network analysis was applied to analyze psychopathological symptoms between three CT subgroups (EA, PA, and SA). Both the edges and centralities were computed, and the network properties were compared among the three subgroups. Results: The results showed that the main symptoms across all three groups are uncontrollable worry, sad mood, irritability, and fatigue, which indicates these core symptoms play essential roles in maintaining the whole psychological symptoms network. Furthermore, there are significant differences between the three groups. When comparing the network structure of the three groups, the SA group is more likely to be associated with PTSD symptoms, the EA group is more likely to be associated with suicide-related symptoms, and the PA group is more likely to be associated with anxiety symptoms. Conclusion: The distinctive core psychopathological symptoms within the networks of the CT subgroups revealed specific symptoms across each group. The results of the current study suggest multiple paths between trauma and psychopathology and may also be useful in mapping potential transdiagnostic processes. It is recommended that schools and local communities should support early intervention to improve psychological well-being among CT survivors.